Предмет: Алгебра,
автор: sashazavyalov2206
(7x-2)(7x+2)=
(2x^2-y^2)(4x^3+2xy+y^3)=
Ответы
Автор ответа:
0
1) (7x-2)(7x+2)=
7x^2-2^2
49x^2-4
2) (2x^2-y^2)(4x^3+2xy+y^3)
2x^2+4x^3•y+2x^2•y^3-4x^3•y^2-2x•y^3-y^5= 8x^5+4x^3•y+2x^2•y^3-2x•y^3-y^5
7x^2-2^2
49x^2-4
2) (2x^2-y^2)(4x^3+2xy+y^3)
2x^2+4x^3•y+2x^2•y^3-4x^3•y^2-2x•y^3-y^5= 8x^5+4x^3•y+2x^2•y^3-2x•y^3-y^5
Похожие вопросы
Предмет: Математика,
автор: mary1075
Предмет: Геометрия,
автор: sabrinahamdamova2
Предмет: Русский язык,
автор: shakirovaa2011
Предмет: Алгебра,
автор: MrGenie